PENGARUH LEVERAGE, UKURAN PERUSAHAAN, LIKUIDITAS TERHADAP YIELD SUKUK DENGAN INFLASI SEBAGAI VARIABEL MODERASI - Alkautsar, Obrin; Susanti, Riana (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to analyze the influence of leverage, company size, and liquidity on sukuk yields and to determine the influence of inflation moderating the relationship between leverage, company size, and liquidity variables on sukuk yields. The data used is Corporate Sukuk through a public offering as of December 2023 on the official website of the Financial Services Authority (OJK), the Indonesia Central Securities Depository (KSEI), the Indonesia Stock Exchange (IDX) and financial statements issued by their respective companies in 2022 – 2023. This research is a comparative causal research, which analyzes the causal relationship between two or more variables. The variables used in this study are several fundamental factors of financial performance, namely Leverage proxied by Debt of Equity (DER), Company Size (Size), and Liquidity proxied by Current Ratio (CR), as independent variables and sukuk yield proxied by Yield To Maturity (YTM) as a dependent variable with Inflation as the moderating variable.  The research population in this study is 54 companies that issue corporate sukuk. This sampling technique uses Purposive Sampling, 30 company samples were obtained. The data processing method used in this study is multiple linear regression analysis test and moderate regression analysis using EViews 12. The results of this study show that leverage (DER), company size, and liquidity simultaneously have no effect on sukuk yield, leverage (DER) partially affects sukuk yield, company size partially has no effect on sukuk yield, liquidity partially has no effect on sukuk yield, and inflation does not strengthen the relationship between leverage, company size, and liquidity to sukuk yield.